Ammodytes personatus Girard 1856 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Ammodytes personatus Girard, 1856. Pacific Sand Lance. To at least 27.4 cm (10.9 in) SL (Orr et al. 2015). Norton Sound, eastern Bering Sea to Attu Island, Aleutian Islands, to Balboa Island, southern California; May range to Sea of Okhotsk (Orr et al. 2015). Near surface to fairly shallow depths and also bury in substrate; depth: intertidal to 272 m (892 ft) (min.: Eschmeyer and Herald 1983; max.: DFO). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 193, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...